Prompting meaningful analysis from pre-service teachers using elementary mathematics video vignettes. (April 2017) - Beilstein, Shereen Oca; Perry, Michelle; Bates, Meg Schleppenbach
Abstract: Learning from video is a theoretically grounded and popular professional development activity. In online professional development communities, however, responses to video are often shallow and lack meaningful commentary about issues that surround teaching and learning mathematics. By altering the framing conditions that accompany video clips posted to the Everyday Mathematics Virtual Learning Community, this study examined whether more deeply analytical comments could be elicited from pre-service teachers. Findings highlight the malleability of pre-service teachers' commentary, as their levels of analysis varied in relation to manipulations of perceived audience (expert or peer) and focus requested (on students, the teacher, or unspecified). Highlights: Seeing short videos (<4 min) can produce analytical comments from pre-service teachers. Participants' responses appear to be malleable and sensitive to prompt types. Participants were most analytical when asked to focus on the teacher portrayed in the video. Participants were most descriptive when asked to focus on the students.